Development of nanoemulgel containing nanobentonite-purified catfish oil for candidate of a wound healing dosage form - Tri Anita Sari, Annis Catur Adi, Heni Rachmawati (Journal of Applied Pharmaceutical Science, 2024)
Catfish oil contains docosahexaenoic acid (DHA) which is a bioactive substance as a burn wound healer. This study aims to improve the organoleptic property of catfish oil using nanobentonite as an adsorbent, then formulated in topical nanoemulgel. Purified catfish oil was prepared into nanoemulsion by self-nanoemulsification method. The nanoemulsion formula consisted of catfish oil, cremophor RH40, and Polyethylene glycol (PEG) 400 with various ratios. The optimized nanoemulsion formula was incorporated into hydrogels which were developed using various polymers. Nanobentonite particle size of 508.47 ± 10.47 nm at 10% had the potential to improve catfish oil organoleptic without significantly reducing DHA level. The good physical appearance of nanoemulsion was produced by a 1:8:1 ratio and showed droplet size of 21.03 ± 0.23 nm, Polydispersity index (PDI) 0.269 ± 0.04, pH 6.83 ± 0.02, and zeta potential of −15 ± 2.57 mV. The most stable nanoemulgel was formed by 2% CMC-Na. This nanoemulgel containing catfish oil nanoemulsion has a particle size of 114.4 ± 2.40 nm, PDI 0.399 ± 0.02, pH 6.89 ± 0.01, viscosity of 5,700 ± 50 cps, spreadability of 5.69 ± 0.08 cm, and shows physicochemically stable at 25°C storage conditions. Thus, nanoemulgel containing catfish oil nanoemulsion is a promising wound healer. Nanobentonite is also a potential adsorbent to improve the acceptability of catfish oil for topical use.
Keywords: Catfish oil, nanobentonite, nanoemulgel, nanoemulsion, wound healing